Implementation and Analysis of Reversible logic Based Arithmetic Logic Unit - Shaveta Thakral; Dipali Bansal; S.K. Chakarvarti (Universitas Ahmad Dahlan, 2016)
There is a tremendous growth in fabrication from small scale integration (SSI) to giant scale integration (GSI). It however raises a question of sustainability of Moore's law due to almost intolerable levels of power consumption. Researchers have invented a lot of methods to reduce power consumption and recent technologies are switching to reversible logic. Reversible logic has various applications in fields of computer graphics, optical information processing, quantum computing, DNA computing, ultra low power CMOS design and communication. Arithmetic Logic Unit (ALU) is considered to be the basic building block of a CPU in the computing environment and portability in computing system highly demands reversible logic based ALU. Modern processors usually have a word length of 32 or 64 bits. Divide and conquer approach principle cascades n number of 1 bit ALU to implement n bit ALU. Several researchers have proposed 1-bit ALU design using various reversible logic gates. This paper aims at categorizing various ways of implementation in VHDL using Xilinx ISE design suit 14.2 tool and comparative analysis of existing 1 bit ALU designs in terms of optimization metrics like power consumption, number of gates, number of constant inputs, number of garbage outputs and quantum cost. ALU realized using carry save adder block is found to be most optimum design in terms of gate count and quantum cost.